Mitofilin Mitigates Myocardial Damage in Acute Myocardial Infarction by Regulating Pyroptosis of Cardiomyocytes - Ma, Min; Liang, Shi-chu; Diao, Kai-yue; Wang, Qin; He, Yong (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute myocardial infarction (AMI) can lead to sudden cardiac death after prolonged ischemia or heart failure and impaired left ventricular pump function. However, the underlying mechanism remains largely unknown. The purpose of this study was to investigate the role of mitofilin in alleviating AMI. Methods: Recombinant adenoviral vectors for mitofilin overexpression or mitofilin knockdown were constructed, respectively. A mouse AMI model was established and the effect of mitofilin on myocardial pyroptosis was examined by detecting lactate dehydrogenase (LDH) and inflammatory factors. Moreover, a cellular model of AMI was established by treating cardiomyocytes with hypoxia/reoxygenation (H/R). Enzyme-linked immunosorbent assay (ELISA) and Western blot were used to detect the effect of mitofilin knockdown on the expression of pyroptosis-related factors. Furthermore, the regulatory role of mitofilin in PI3K/AKT pathway was evaluated by Western blot and PI3K inhibitor. Results: Mitofilin was down-regulated in the heart tissue of AMI mouse and H/R induced cardiomyocytes. The overexpression of mitofilin significantly alleviated AMI and reduced pyroptosis-related factors. Meanwhile, in cardiomyocytes mitofilin knockdown aggravated cellular damages by promoting pyroptosis. Further analysis showed that the anti-pyroptotic effect of mitofilin was dependent on the activation of PI3K/AKT signaling pathway. Conclusions: Our study suggests that mitofilin regulates pyroptosis through PI3K/AKT signaling pathway in cardiomyocytes to ameliorate AMI, which may serve as a therapeutic strategy for the management of AMI.